Theoretical Investigation of the Deactivation of Ni Supported Catalysts for the Catalytic Deoxygenation of Palm Oil for Green Diesel Production - Sanaa Hafeez (Catalysts, 2021)
For the first time, a fully comprehensive heterogeneous computational fluid dynamic (CFD) model has been developed to predict the selective catalytic deoxygenation of palm oil to produce green diesel over an Ni/ZrO2 catalyst. The modelling results were compared to experimental data, and a very good validation was obtained. It was found that for the Ni/ZrO2 catalyst, the paraffin conversion increased with temperature, reaching a maximum value (>95%) at 300 °C. However, temperatures greater than 300 °C resulted in a loss of conversion due to the fact of catalyst deactivation. In addition, at longer times, the model predicted that the catalyst activity would decline faster at temperatures higher than 250 °C. The CFD model was able to predict this deactivation by relating the catalytic activity with the reaction temperature.